A case of secondary abdominal ectopic pregnancy in a bitch. Issue 1 (22nd November 2021) - Yenilmez, Kudret; Dogan, Halef
Abstract: Cases of ectopic pregnancy (EP) and associated fetal mumification in bitches have been rarely reported. In this case report, it was aimed to present a case of secondary abdominal EP diagnosed in a 3‐year‐old bitch. Abdominal EP was incidentally diagnosed by radiographic examination of the bitch, which had a traffic accident, for likely possible fractures in the body. This case, which can be classified as secondary abdominal EP, was found to be compatible with the literature. The ectopic fetuses were removed from the body by surgical method, and the bitch was fully recovered.